Suppression of puberty with GnRH analogues in adolescents with Gender Dysphoria - Poleszak, Julita; Szabat, Przemysław; Szabat, Marta; Wójcik, Magdalena; Boreński, Grzegorz; Janowska, Małgorzata; Karakuła-Juchnowicz, Hanna (Journal of Education, Health and Sport, 2019)
Introduction: Gender Dysphoria (GD) is defined as a mismatch between biological sex characteristics and gender identity. The percentage of teenagers with doubts about their gender identity has dramatically increased over the past decade.The aim of the study: This article presents the positions of supporters and opponents regarding suppression of puberty with GnRH analogues in GD adolescents.Material and method: Standard criteria were used to review the literature data. The search of articles in the PubMed database was carried out using the following keywords: gender dysphoria, transsexualism, suppression of puberty.Description: Due to the extension of the time needed to shape gender identity, suppression of puberty seems to be a beneficial preventive measure for the development of sexual dysphoria. Adolescents avoid suffering associated with the development of unwanted sex. However, there are numerous concerns about the negative effects of puberty inhibition on bone development, neuropsychological development and future fertility.Summary: The safety and effectiveness of therapy that inhibits puberty is not properly grounded in scientific evidence. There is still a lack of research assessing the long-term effects of administering hormones that interfere with adolescent sexual development.